2007
DOI: 10.1099/mic.0.2007/006122-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pseudomonas aeruginosa quorum sensing on biofilm persistence in an in vivo intraperitoneal foreign-body infection model

Abstract: Pseudomonas aeruginosa is an opportunistic human pathogen that causes chronic biofilm-based infections in host organisms. P. aeruginosa employs quorum sensing (QS) to control expression of its virulence, and to establish and maintain chronic infections. Under such conditions, the biofilm mode of growth contributes significantly to P. aeruginosa tolerance to the action of the innate and adaptive defence system and numerous antibiotics. In the present study, an in vivo foreign-body infection model was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 46 publications
3
88
0
1
Order By: Relevance
“…Diverse sets of furanone compounds have been generated by chemical synthesis (237,238), yielding inhibitors tested most frequently and rigorously on P. aeruginosa quorum sensing and on the V. fischeri LuxR protein heterologously expressed in E. coli, where compounds C-30 and C-56 (Table 3) were the most effective inhibitors (134,237,(239)(240)(241)(242)(243). More recently, additional synthetic schemes have led to new varieties of furanones, but their inhibitory properties remain relatively untested (244,245).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…Diverse sets of furanone compounds have been generated by chemical synthesis (237,238), yielding inhibitors tested most frequently and rigorously on P. aeruginosa quorum sensing and on the V. fischeri LuxR protein heterologously expressed in E. coli, where compounds C-30 and C-56 (Table 3) were the most effective inhibitors (134,237,(239)(240)(241)(242)(243). More recently, additional synthetic schemes have led to new varieties of furanones, but their inhibitory properties remain relatively untested (244,245).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…QS-deficient P. aeruginosa strains show a clear reduction in overall pathogenicity (Christensen et al, 2007;Mittal et al, 2006). It has also been shown that in clinical P. aeruginosa isolates various components of the QS circuit have been lost due to mutations.…”
Section: Discussionmentioning
confidence: 99%
“…based on the implantation of silicone chips pre-colonized with P. aeruginosa into lungs of mice has also demonstrated that a functional QS system is critical for the establishment of infection (Christensen et al, 2007). However, a number of studies have demonstrated that QS mutants can be isolated from CF samples.…”
Section: Identification Of Qs Signals and Regulated Products From CLImentioning
confidence: 99%